Interests and Purposes in Conceptions of Autonomy - Nickel, Jodi Lee (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
This article examines conceptions of autonomy outlined by Dearden, Callan, Dewey and Kerr and distinguishes between five conceptions, namely, belief autonomy, action autonomy, interest autonomy, purpose autonomy and social autonomy. While Kerr criticizes conceptions of autonomy which are not explicitly moral, this article argues that the emphasis in some philosophical literature has simply emphasized self-regarding virtues more than other-regarding virtues. Purpose autonomy is considered a rich conception of autonomy because it not only builds upon children’s interests but provides the initiative and continuity to sustain interest even in challenging circumstances.